Road Election Decision Support System to Work in East Jakarta - Priangga Sotya W; Paundra Nabillah; Indrawan, Bintang; Desti Fitriati (Universitas Pancasila, 2022)
The increase in the number of roads is increasingly related to the number of kendarana volumes that must be carried out. This condition results in roads, especially the East Jakarta area, causing a buildup at certain titk points. This study aims to determine the best road to travel in order to avoid severe congestion alternatives. The trick is to give the decision to choose the road to be traveled smoothly with a low level of busyness of the road at least jammed under normal conditions. To determine the best path based on many criteria considerations, where the criteria can be measured quantitatively with the Exponential method, method Simple Additive Weighting (SAW) and method Weighted Product (WP). 3 Methods are used to numerically assess the priority value of each selected path , because this method is able to prioritize optimal alternatives. Usingcalculations can make it easier for vehicle users, especially the East Jakarta area, to choose roads that have low density for various types of problems to be analyzed. This test was conducted on 3 road datasets in 2014. With this system will help the path to make decisions more subjectively